PEMAKAIAN ALKOHOL PADA OBAT BATUK SIRUP BERDASARKAN 4 MAZHAB - Hani, Umi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
The research objectives are 1) the level of alcohol that is put on the drug. 2) The use of alcohol in cough medicine is based on 4 schools. The type is done by library research with the type of research is descriptive normative. Sources of data in this study consisted of two kinds, namely primary data and secondary data. Data analysis using qualitative conducted using the deductive method. Descriptive methods are used to describe how renters practice being transferred before maturity. The results of the study that alcohol content contained in cough medicine is legal (permissible), because basically the hadith of the prophet about the prohibited khamar is in the context of drinks that already contain intoxicating elements, so if taken in small or large amounts the law is haram. Whereas in terms of its use as a solvent in cough medicine it is not the case if the levels remain within the prescribed limits ie not more than 1%. According to four Imam Mazhab (Imam Hanafi, Imam Maliki, Imam Shafi, i and Imam Hambali) agreed that alcohol is unclean as khamar because they are both intoxicating. But the authors of cough medicines that contain alcohol are legal and permissible, but do not contain dependence on consuming these drugs and are not intoxicating and only for healing.